2021
DOI: 10.3389/fcvm.2021.627873
|View full text |Cite
|
Sign up to set email alerts
|

Essential Genes and MiRNA–mRNA Network Contributing to the Pathogenesis of Idiopathic Pulmonary Arterial Hypertension

Abstract: Background: Idiopathic pulmonary arterial hypertension (IPAH) is a life-threatening disease. Owing to its high fatality rate and narrow therapeutic options, identification of the pathogenic mechanisms of IPAH is becoming increasingly important.Methods: In our research, we utilized the robust rank aggregation (RRA) method to integrate four eligible pulmonary arterial hypertension (PAH) microarray datasets and identified the significant differentially expressed genes (DEGs) between IPAH and normal samples. Gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Inflammation, including macrophages recruited early in PAH and activities of various cytokines or chemokines, is being deemed as a major contributor to the pathogenesis of PAH (3). Several researchers have indicated that a wide variety of chemokine systems comprising the CCL2-CCR2, CX3CL1-CX3CR1 and CCL5-CCR5 axis involved in macrophage recruitment and pulmonary vascular remodeling (6)(7)(8). Even several chemokines, for example, CCL2 and CXCL10, have emerged as potential biomarkers of PAH due to the elevating trend in disease setting and their correlation with disease severity in different forms of PAH (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation, including macrophages recruited early in PAH and activities of various cytokines or chemokines, is being deemed as a major contributor to the pathogenesis of PAH (3). Several researchers have indicated that a wide variety of chemokine systems comprising the CCL2-CCR2, CX3CL1-CX3CR1 and CCL5-CCR5 axis involved in macrophage recruitment and pulmonary vascular remodeling (6)(7)(8). Even several chemokines, for example, CCL2 and CXCL10, have emerged as potential biomarkers of PAH due to the elevating trend in disease setting and their correlation with disease severity in different forms of PAH (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNA-mRNA network contributes to the pathogenesis of idiopathic pulmonary arterial hypertension [ 28 ]. In this study, bioinformatics analysis indicated that NOS1 might be a direct downstream target of miR-4640-5p.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed a connection between idiopathic pulmonary arterial hypertension (IPAH) and and miR-34b-5p, which was associated with most of the declinable target differentially expressed genes, cell multiplication, and adhesion-independent growth [ 68 ]. The target genes of miR-34b-5p are basically related to immune and inflammatory reactions, for instance, neutrophil chemotaxis and migration, integrin binding, and Toll-like receptor binding [ 69 , 70 ]. Besides, they are also involved in inflammation pathways such as the IL-17 signaling pathway, indicating that miR-34b-5p might play crucial roles in the pathogenesis of IPAH through enhanced inflammatory response [ 71 ].…”
Section: Mir-34b-5p In Injurymentioning
confidence: 99%